Penyuluhan Pemilihan Makanan yang Tepat untuk Menjaga Kadar Glukosa Darah dan Tekanan Darah pada PROLANIS - Mustikaningrum, Fitriana; Kisnawaty, Sudrajah Warajati (Abdi Geomedisains, 2024)
The PROLANIS is a program conducted by Ngemplak 1 Primary Health Care that gives general clinical examination and activity for patients with diabetes and hypertension.  The participants of the PROLANIS program are elderly people with age 50 years old. The nutrition knowledge of PROLANIS members was low, which led them to often ask about good food to maintain blood glucose and blood pressure remained normal. However, the activities to increase knowledge about diet are rarely carried out due to limited human resources at Ngemplak 1 Primary Health Care. Therefore, the counselling method using pocket books about food choices to maintain normal blood glucose levels and blood pressure is carried out to increase knowledge and is expected to improve the quality of life of PROLANIS members. At the end of the session, participants were given a questionnaire to select recommended and restricted foods to manage blood glucose and blood pressure. The result showed that more than 50% of the participants answered the question correctly. This indicated that more than 50% of the participants had understood the counselling materials.